The Acculturation of Local and Shia Cultures in the Tabot Tradition of Bengkulu - Ilma Nailu Fitriani Ilma (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study applies J. Powell’s theory of acculturation to analyze the cultural synthesis in the Tabot ceremony, examining the mutual influences between Shia traditions and Bengkulu’s indigenous practices. Utilizing a descriptive-qualitative methodology, the research involves comprehensive library research for historical and cultural contexts, complemented by fieldwork with the Kerukunan Keluarga Tabot (KTT), the tradition’s custodians. Data analysis follows a structured three-stage process: reduction, display, and conclusion drawing/verification. This approach ensures a thorough and accurate interpretation of findings. The Tabot ceremony commemorates the martyrdom of Prophet Muhammad’s grandson, Hussein bin Ali bin Abi Talib, in the battle against Ubaidillah bin Zaid’s forces in Karbala, Iraq, on the 10th of Muharram, 61 Hijri (681 AD). Initiated by Sheikh Burhanuddin, also known as Imam Senggolo, in 1685, the first Tabot celebration marked his union with a Bengkulu native, founding the Tabot lineage. This annual event spans from the 1st to the 10th of Muharram. Although originally a Shia Islamic rite, the Tabot ceremony transformed under the influence of Sunni Islam in Bengkulu, leading the descendants of Shia propagators to fervently adopt Sunni Islam. Despite this shift, they continue to observe the Tabot Ritual as a “universal Islamic religious rite” highlighting the doctrinal harmony between Shia and Sunni Islam. Thus, the Tabot Ritual is upheld as crucial for preserving and perpetuating ancestral heritage